Influence of Stress on Electronic and Optical Properties of Rocksalt and Wurtzite MgO–ZnO Nanocomposites with Varying Concentrations of Magnesium and Zinc - Lin, Yin-Pai; Piskunov, Sergei; Trinkler, Laima; Chou, Mitch Ming-Chi; Chang, Liuwen (MDPI, 2022)
The structural, electronic and optical properties of stressed MgO–ZnO nanocomposite alloys with concentrations of Zn and Mg varying from 0.125 to 0.875 were studied using ab initio simulations. Two crystal structures are considered for the initial MgO–ZnO alloys: the rocksalt Mg (Formula presented.) Zn (Formula presented.) O and wurtzite Zn (Formula presented.) Mg (Formula presented.) O phases. For rocksalt Mg (Formula presented.) Zn (Formula presented.) O, the optimized structures are stable at pressures below 10 GPa. The larger the Mg concentration and pressure, the wider the (Formula presented.) of the rocksalt phase. In contrast, the optimal geometries of wurtzite Zn (Formula presented.) Mg (Formula presented.) O reveal a diversity of possibilities, including rocksalt, wurtzite and mixed phases. These effects lead to the fact that the optical properties of wurtzite Zn (Formula presented.) Mg (Formula presented.) O not only demonstrate the properties of the wurtzite phase but also indicate the optical features of the rocksalt phase. In addition, mixed phases of Zn (Formula presented.) Mg (Formula presented.) O simultaneously provide the characteristics of both wurtzite and rocksalt phases with the same structures in different dielectric matrices. © 2022 by the authors. --//-- This is an open access publication Lin Y.-P., Piskunov S., Trinkler L., Chou M.M.-C., Chang L. "Influence of Stress on Electronic and Optical Properties of Rocksalt and Wurtzite MgO–ZnO Nanocomposites with Varying Concentrations of Magnesium and Zinc" (2022) Nanomaterials, 12 (19), art. no. 3408, DOI: 10.3390/nano12193408 published under the CC BY 4.0 licence.
The financial support of M-ERA.NET project “ZnMgO materials with tunable band gap for solar-blind UV sensors” (ZMOMUVS) is greatly acknowledged. The Institute of Solid State Physics, University of Latvia, as the Center of Excellence, has received funding from the European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement no. 739508, project CAMART2. The calculations were performed at the Latvian SuperCluster (LASC) located at the Institute of Solid State Physics, University of Latvia.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; MgO–ZnO alloys; optical properties; pressure; rocksalt Mg1−xZnxO; wurtzite Zn1−xMgxO